Evaluasi Kinerja Tenaga Honorer Dalam Meningkatkan Kualitas Pelayanan Pada Dinas Kepemudaan, Olahraga, Dan Pariwisata Kabupaten Banyuasin - Femi Asteriniah (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
In an effort to improve public services, the quality of human resources must also be improved, because human resources have an important role in the success of achieving organizational goals. The excellence of an organization depends on the ability of the organization to achieve optimal performance. Good performance will be achieved if the performance of employees working in the organization is progressing or increasing. To achieve the expected employee performance, the organization really needs to examine what factors affect the performance of its employees. In this study, the researcher intends to obtain an in-depth and comprehensive picture of honorary staff in improving the quality of service at the Office of Youth, Sports and Tourism of Banyuasin Regency. The approach used in this study is a qualitative approach. Based on research at the Banyuasin Regency Youth, Sports and Tourism Office, the attitude of honorary officers in implementing services at the Banyuasin Regency Youth, Sports and Tourism Office is quite good. In relation to the assessment or perception of employees, honorary staff are quite responsive to complaints or needs in the implementation of services at the Youth, Sports and Tourism Office of Banyuasin Regency. Government officials as elements of the state apparatus in carrying out the wheels of government are required to carry out their functions and duties as state servants and public servants. Employees must also be able to uphold the dignity and image of employment for the benefit of society and the state, but the reality on the ground speaks differently where there are still many employees who are not aware of their duties and functions so that inequalities often arise in carrying out their duties. Keywords: Performance Evaluation, Honorary Personnel, Service Quality